Liquid-metal-elastomer foam for moldable multi-functional triboelectric energy harvesting and force sensing. (October 2019) - Nayak, Suryakanta; Li, Yida; Tay, Willie; Zamburg, Evgeny; Singh, Devendra; Lee, Chengkuo; Koh, Soo Jin Adrian; Chia, Patrick; Thean, Aaron Voon-Yew
Abstract: This article reports on a moldable soft porous composite of liquid metal alloy (LMA) and Ecoflex-0030 elastomer for the first time, where random pores in the composite behaves as tiny triboelectric nanogenerators (TENGs). The triboelectric foam produced a maximum peak-to-peak short-circuit current (ISC ) of 466 nA (charge density = 35 μC/m 2 ) and open circuit voltage (VOC ) of 78 V for a sample of size 5 cm × 5 cm × 1 cm, where the output current is 20% higher than previously reported triboelectric foams based on PDMS and lead zirconate titanate (PZT)/carbon nanotube (CNT) of equivalent area. In addition, surface texture further increases the foam's softness and enhance the charge generation leading to a 36% increase in triboelectric charge (charge density = 48 μC/m 2 ). A soft monolithic shoe insole is prepared, which produced a range of triboelectric responses in the order of μA in response to different modes of human motion. Upon jogging, the porous shoe insole with 3 wt parts of LMA in Ecoflex matrix, produce an instantaneous power of 2.6 mW (instantaneous power density = 13 μW/cm 2 ). In addition, the insole also shows capacitive response to deformation, enabling the sensor to perform in-motion force and weight measurement. Graphical abstract: Image 1 Highlights: The triboelectric Ecoflex-Galinstan foam produced a maximum peak-to-peak short-circuit current (ISC ) of 466 nA (charge density = 35 μC/m 2 ) and open circuit voltage (VOC ) of 78 V for a sample of size 5 cm × 5 cm × 1 cm subjected to 5 mm compression-relaxation cycles, where the output current is 20% higher than previously reported triboelectric foams based on PDMS and PZT/CNT of equivalent area. The shoe insole produces an instantaneous power of 2.6 mW (power density = 13 μW/cm 2 ) in case of jogging, which can be used to power electrocardiogram (ECG) chips and other small-scale wearable sensors. There is change in capacitance with loading of different static or cyclic forces. So, this type of composites can be used as weight/force measurement sensor.